2013
DOI: 10.3390/s131114558
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Quorum Sensing Activity of the Traditional Chinese Herb, Phyllanthus amarus

Abstract: The discovery of quorum sensing in Proteobacteria and its function in regulating virulence determinants makes it an attractive alternative towards attenuation of bacterial pathogens. In this study, crude extracts of Phyllanthus amarus Schumach. & Thonn, a traditional Chinese herb, were screened for their anti-quorum sensing properties through a series of bioassays. Only the methanolic extract of P. amarus exhibited anti-quorum sensing activity, whereby it interrupted the ability of Chromobacterium violaceum CV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 39 publications
(56 reference statements)
0
19
0
Order By: Relevance
“…Jamming of QS by IM from minced beef, salami, soft cheese, fresh salad, and chicken pâté (for example, LAB, Brochothrix thermosphacta , Pseudomonas spp., Enterobacteriaceae, and enterococci) could reduce the L. monocytogenes biofilms formation (Al‐Zeyara and others ). Anti‐QS strategies have been studied and reported by Priya and others (). Phytochemicals are also reported to possess anti‐QS and antibiofilm activities in different microorganisms such as Y. enterocolitica and Erwinia carotovora (Truchado and others ), Chromobacterium violaceum (Borges and others ), and E. coli O157:H7 (Lee and others ).…”
Section: Novel Concepts For the Control Of Mixed‐species Biofilmsmentioning
confidence: 99%
“…Jamming of QS by IM from minced beef, salami, soft cheese, fresh salad, and chicken pâté (for example, LAB, Brochothrix thermosphacta , Pseudomonas spp., Enterobacteriaceae, and enterococci) could reduce the L. monocytogenes biofilms formation (Al‐Zeyara and others ). Anti‐QS strategies have been studied and reported by Priya and others (). Phytochemicals are also reported to possess anti‐QS and antibiofilm activities in different microorganisms such as Y. enterocolitica and Erwinia carotovora (Truchado and others ), Chromobacterium violaceum (Borges and others ), and E. coli O157:H7 (Lee and others ).…”
Section: Novel Concepts For the Control Of Mixed‐species Biofilmsmentioning
confidence: 99%
“…Crude extracts of many plant parts were shown to possess anti-QS activity using C. violaceum as a model bacterium [19], [20], [21]. Crude plant extracts are often found to be more effective than isolated constituents at an equivalent dose perhaps owing to positive interactions between components of whole plant extracts.…”
Section: Introductionmentioning
confidence: 99%
“…25 There are several reports in literature that propose different mechanisms of quorum sensing inhibition by natural products, either by inhibition of the signal molecule biosynthesis, 26 preventing the binding of the AHL molecules to its receptors 6 or enzymatic inactivation and biodegradation of the quorum sensing signalling molecules. 5 Study from Zahin et al 13 Chong et al 28 and Priya et al 29 also revealed quorum sensing property of Mangifera indica, Punica granatum, Myristica cinnamomea and Phyllanthus amarus, which showed efficacy in regulating violacein production of C. violaceum and inhibiting motility of P. aeruginosa. The result in our study have revealed that the ethanol extract of T. catappa leaves and A. alitilis flower significantly inhibit the quorum sensing mechanism of P. aeruginosa PAO1 as indicated by a reduction in pyocyanin production, inhibition of P. aeruginosa motility, reduction in LasA protease production and inhibition of P. aeruginosa biofilm formation which is an important trait for its pathogenicity.…”
mentioning
confidence: 98%